Improving Student Learning Outcomes with the Drill Method in PAI Subjects at SDN 04 Bukit Malintang Elementary School - Lusi Halizani Fitri (BiCED Proceeding, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) for fourth-grade students at SD Negeri 04 Bukit Malintang through the application of the Drill method. This classroom action research (CAR) was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. In the first cycle, student learning outcomes showed improvement, with six out of ten students achieving the minimum competency criteria (KKM). However, some students still struggled to grasp the material and were not actively engaged in learning. The second cycle involved enhancements to the explanation of the Drill method, the development of more systematic teaching modules, and the management of group discussions. As a result, all students (100%) met the KKM with an average score above 75. Both student and teacher activities during learning also showed significant improvement based on observations. This study concludes that the Drill method is effective in enhancing students’ learning outcomes, both cognitively and in terms of active participation. The study recommends using the Drill method as an active learning strategy for PAI subjects.